2016
DOI: 10.20510/ukjpb/4/i4/110647
|View full text |Cite
|
Sign up to set email alerts
|

Ulcer Healing Mechanism of Ethanolic Extract of Talinium triangulare in Male Wistar Rats

Abstract: Talinium triangulare have been proven to offer promising antiulcer properties which could validate its"folkoric use for the treatment of gastric ulcer in various part of Nigeria. This study investigates the role of methanolic extract of Talinium triangulare (METT) in gastric ulcer healing and the possible mechanisms involved. Twenty-eight male wistar rats (160-180gm, n=7) were grouped into; A-control, B-ulcerated untreated, C-ulcerated treated with Omeprazole (20 mg/kg b.w.) and D-ulcerated treated with METT (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…Conversely, Pereira et al [58] reported an increase in the number of proliferating cells when they assessed PCNA in rats treated with a bark extract of Tabebuia avellanedae after induction of chronic ulcers using acetic acid. The report of the present study was however similar to that published by Ajayi et al [59]. In their study, there was no difference in expression of Ki67 between rats treated for chronic ulcer using ethanolic extract of Talinium triangulare and the untreated ones.…”
Section: Effect Of Administration Of Fractions On the Expression Of Pecam-1 In The Gastric Mucosa Of Treated Animalssupporting
confidence: 91%
See 1 more Smart Citation
“…Conversely, Pereira et al [58] reported an increase in the number of proliferating cells when they assessed PCNA in rats treated with a bark extract of Tabebuia avellanedae after induction of chronic ulcers using acetic acid. The report of the present study was however similar to that published by Ajayi et al [59]. In their study, there was no difference in expression of Ki67 between rats treated for chronic ulcer using ethanolic extract of Talinium triangulare and the untreated ones.…”
Section: Effect Of Administration Of Fractions On the Expression Of Pecam-1 In The Gastric Mucosa Of Treated Animalssupporting
confidence: 91%
“…As discussed earlier, alkaloids are one of the polyphenols known to alter blood flow and may have played a role in this case via a yet to be established mechanism [39]. The higher expression of PECAM-1 in this study is similar to the report by Ajayi et al [59] in which the treatment of chronic ulcers induced by acetic acid was performed with ethanolic extract of Talinium triangulare. They reported an increase in the expression of PECAM-1 in the gastric mucosa of treated rats compared to untreated.…”
Section: Effect Of Administration Of Fractions On the Expression Of Pecam-1 In The Gastric Mucosa Of Treated Animalssupporting
confidence: 88%
“…Gastric ulcers were induced using acetic acid following the method described by Ajayi et al [ 29 ] with a little modification. There was no food in the animal's cages 24 h before the induction procedure, and then the stomach of each rat was exposed under anaesthesia [a mixture of xylazine (0.0005 ml/g b.w) and ketamine (0.0015 ml/g b.w)] by performing laparotomy through a midline epigastric incision.…”
Section: Methodsmentioning
confidence: 99%
“…Peptic ulcer is a consequence of an imbalance between aggressive factors such as acid, pepsin, nonsteroidal anti-inflammatory medications and mucosal defence system (74,75). To evaluate the antiulcer activity of T. triangulare, leaves were harvested from the local garden at Faculty of Agricultural Sciences, LAUTech, Ogbomoso, Nigeria (75). The plants were scientifically identified, processed, and extracted according to known methods.…”
Section: Gastrointestinal Activity Of T Triangularementioning
confidence: 99%